The Influence of Beauty Influencers, Brand Image, and Price on Customer Loyalty for OMG Cosmetic Products in Surabaya - Kirana Yuni Susanti; Indah Respati Kusumasari (LP2M IAIN Palopo, 2026)
The rapid digital transformation in Indonesia has fundamentally shifted social media into a primary source of brand information, significantly impacting the competitive local cosmetic industry. Despite high sales volumes, brands like OMG (Oh My Glam) face challenges with high brand-switching behavior and rising consumer vigilance regarding product safety. This study aims to analyze the influence of Beauty Influencers, Brand Image, and Price on the Customer Loyalty of OMG cosmetic products in Surabaya. Using a quantitative approach, data were collected from 100 respondents through questionnaires and analyzed using multiple linear regression. The results of the F-test confirm that Beauty Influencers, Brand Image, and Price simultaneously exert a significant positive influence on Customer Loyalty. Partially, the T-test results indicate that each variable has a significant individual impact on loyalty. Beauty influencers build trust through credible recommendations, a positive brand image encourages long-term commitment, and affordable pricing stimulates repeat purchases. The synergy of these three marketing elements is a major determinant of consumer retention in a trend-driven market. This study suggests that brands should maintain beauty influencer credibility, positive brand image and competitive pricing strategies to mitigate external risks and strengthen long-term loyalty in the digital-first era.